Zachowania samobójcze w rodzinach. Społeczne konsekwencje zjawiska - Czabański, Adam (Teologia i Moralność, 2020)
In 2017, 5276 people committed suicide in Poland, while suicide attempts were reported by at least 50-75 thousand people in Poland. Mourning for a close deceased each year affects 100,000 members of our society. Suicidal behavior causes numerous changes in the functioning of families. A significant part of these changes brings conflicts and deconstruction of families. This is confirmed by research conducted among 146 students of Poznań universities who have experienced suicide of a family member.